The Level of Libyan EFL English Teacher’s Anxiety and its Effect on their Performance (Comprehensive Journal of Science, 2026)
This study aimed to investigate the level of English language teaching anxiety among faculty members in Libyan universities (Universities of Zawia and Sabratha) and to determine its impact on their job performance. Additionally, it sought to identify differences in anxiety levels based on demographic variables, including gender, age, and years of experience. The study employed a descriptive-analytical methodology , and the research instruments were applied to a sample of (34) faculty members.The findings revealed that the overall level of teaching anxiety among the sample was generally moderate. The results also indicated a low impact of teaching anxiety on job performance , suggesting that faculty members possess a high capacity to separate psychological stressors from their professional commitments. Regarding demographic variables, statistical tests (T-test and ANOVA) demonstrated no statistically significant differences in anxiety levels attributable to gender , age , or years of experience. This reflects that teaching anxiety is a shared professional phenomenon that transcends individual and occupational backgrounds. The study recommended providing psychological support programs and training workshops to enhance coping mechanisms for the pressures of university teaching